Too much fighting on the dance floor : retour sur une époque troublée au travers du Ghost Town des Specials - Gildas Lescop (Criminocorpus)
In 1979, the Specials will introduce a dynamic and antiracist scene by mixing punk rock energy to Jamaican rythms which will make it prone to dance and initiate reflexion to a British youth then subjected to the growing influence of the National Front. In 1981, they will issue another chart ranking song, « Ghost Town », about a desillusioned country stricken by unemployment and violence. The tour following the record launching was punctutated by several brawls within concert goers meanwhile street riots will ignite on several occasions. Hailed by the music press for the pertinence of his social comment, “Ghost Town” will mark the end of an era and will remain as the musical testimony of a troubled period.